Context of Violence in Adolescence Cohort (CoVAC) study: protocol for a mixed methods longitudinal study in Uganda - Karen Devries; Jenny Parkes; Louise Knight; Elizabeth Allen; Sophie Namy; Simone Datzberger; Winifred Nalukenge; Lydia Atuhaire; Nambusi Kyegombe; Eddy Walakira; Janet Seeley; Helen A. Weiss; et al. (BMC, 2020)
Abstract Background Violence exposure in adolescence is associated with a range of poor health and social outcomes, including both the perpetration and experience of violence in later intimate relationships. However, there is little longitudinal evidence on how both individual and contextual characteristics encourage or interrupt these associations. We designed the Contexts of Violence in Adolescence Cohort study (CoVAC) to provide evidence on these pathways for Ugandan adolescents, with the aim of providing information to improve the design of violence prevention interventions for adolescents and young adults. Methods CoVAC is a mixed-methods prospective cohort study with three parallel strands. Between 2014 and 2022, the study comprises three waves of quantitative survey data collection; qualitative data from five time points; and a series of workshops to facilitate direct use of emerging findings by intervention developers at Uganda-based NGO Raising Voices in their ongoing work to prevent violence. 3431 adolescents participated in a survey in 2014 when the majority were aged 11-14 years, and agreed to be re-contacted for a Wave 2 survey in 2018 (aged about 15-18 years); and again in 2021 (aged 18-21 years). 36 young people from Wave 1 survey sample will be invited to participate in longitudinal qualitative data collection. Adolescents aged 18 years and over will provide informed consent; for those under age 18 years, adolescents will be invited to assent, except in cases where caregivers, following notification, have opted not to consent to their adolescent's participation. Quantitative and qualitative data will be analysed iteratively, and triangulation will be used to confirm, clarify and deepen our interpretation of findings. We will hold regular structured meetings so that emerging findings can be integrated into intervention development. Discussion This will be the first longitudinal study on the aetiology of violence over adolescence in sub-Saharan Africa which will enable examination of pathways using mixed methods at multiple time points. Quantitative mediation analysis, and annual qualitative fieldwork will provide detailed insights into how adolescents' violence-related experiences, perspectives and practices relate to their social contexts and how these change over time. Results will feed directly into intervention development to reduce violence and harmful sequelae. Trial registration This study is a long-term follow up of participants in the Good Schools Study (NCT01678846, clinicaltrials.gov). This protocol is for cohort follow-up only; we have a separate protocol paper describing an evaluation of the long-term effects of the Good School Toolkit (In preparation).